Mechanistic classification of cement treated base in Western Australia - Yeo, Yang Sheng; Jitsangiam, Peerapong; Nikraz, Hamid (ICMS Pty Ltd, 2010)
Cement treated crushed rocks are increasingly seen as viable pavement materials capable of meeting increasing loads of current traffic conditions. Cement treatment of crushed rocks forms interlocking matrices between aggregates, altering the physical construct of the material. The change in properties ultimately leads to improved mechanical performance allowing otherwise mechanically unsuitable materials to be selected as sound pavement base. In Australia, the mechanistic-empirical design approach for flexible pavements considers the strength and stiffness developed by cementitiously bound materials by taking into account the flexural modulus of the composite material, Ef. The distinction between bound or unbound material is therefore pivotal to streamline the design process. Current Austroad guidelines for the classification of cement treated base are dependent on the Unconfined Compressive Strength (UCS). Limitations exist in classifying materials with UCS alone, especially in Western Australia (WA) where there are limited studies on mechanistic characterisation of cement treated crushed rocks. This paper provides a regression analysis between UCS and flexural modulus of WA quarried crushed rocks to quantify the cement content which separates bound from unbound behaviour. Variability in sample preparation and testing methods in determining flexural modulus has been known to cause inconsistent results. In response, this investigation applies recent developments in pavement testing regimes for Indirect Tensile Tests and Flexural Beam Test. The relationship between UCS and flexural modulus of cement treated crushed rock as a function of cement content is established, providing a more realistic assumption of the behaviour of cement treated crushed rocks in WA.